Rebuilding Ukraine from a South Korean Perspective: Sharing Experience and Pursuing Shared Growth - Hong, Sogu (Archives of Business Research, 2025)
The goal of this paper is to contribute to the ongoing global discussion on participation in the reconstruction of Ukraine, and it focuses on the following three topics: First, this study shares the experiences and lessons learned from the post-war recovery of South Korea and explains its position on the reconstruction project in Ukraine. Second, this study examines the discussions on postwar reconstruction of Ukraine that are taking place in the international community and identify the direction of reconstruction in Ukraine. Third, it investigates the scale, field, and direction of Korea's support for Ukraine and analyze its characteristics and limitations. Finally, it proposes ways to participate in reconstruction projects that can be helpful to the Korean government, companies, and Ukraine.